The Present and Future of Local Development - Radovanović, Tihomir; Stojmirović, Ljubiša (Napredak, 2020)
The present scientific paper discusses the issues of the local and overall national development so far and in the upcoming period in the context of the world facing increasing general threats (military, terrorist, climate, migrant, pandemic, global, etc.). The obtained research results indicate the urgent need for setting up adequate world organisations and their acting to combat and eliminate these dangers. The results also point out to the appropriate further national and local development, which should be based on a new scientific theory of integrated local and overall social development in each country. It is within this context that Serbia was taken as an example, in the local development of which there are certain problems that practically all countries in the world are facing, so the way out is in the transition to scientifically based integrated local development.
Keywords: local self-government; world changes; integrated development; specificities of Serbia; effects